Edukasi Kesehatan Berbasis Simulasi P3K pada Remaja di SMA Negeri 9 Pekanbaru - Soraya, Soraya; Muhammad, Nanda Noor; Widiyanto, Agung Panji; Prajogi, Peregrinus Adhitira; Fayyas, Dost; Arika, Arika; Sianturi, Marni Sianturi (LPPM UMRI, 2026)
Accidents in school environments can occur unexpectedly and require quick and appropriate first aid response. This study aimed to evaluate the effectiveness of simulation-based health education in improving knowledge and first aid skills among adolescents in secondary school. Methods:A quasi-experimental study was conducted with 33 students from class XII SMA Negeri 9 Pekanbaru. Intervention consisted of interactive lectures, demonstrations, and practical simulations on various types of accidents (bleeding wounds, burns, nosebleeds, fainting, and choking). Knowledge was assessed using pretest and posttest, while skills were evaluated through observation during practical sessions. Results: Significant increase in knowledge scores from pretest to posttest. Observationally, students demonstrated improved confidence and competence in recognizing accidents, applying safety principles, and delivering appropriate first aid techniques.Simulation-based health education is effective in improving knowledge and skills related to first aid among secondary school students. Should be implemented as a routine component of school health programs and can serve as a model for replication in other schools.